A review of theories and models of job burnout in education - Zarei, Yasaman; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
This paper discusses about job burnout, one of the vital work-related problems, which has been studied for many years. Many people in both developed and developing countries might experience some degrees of burnout in their working life. This would have negative effect both for the individual and the organization the individual work for.